Comprehensive geriatric assessment on an acute medical unit: a qualitative study of older people's and informal carer's perspectives of the care and treatment received. (January 2017) - Darby, Janet; Williamson, Tracey; Logan, Pip; Gladman, John
Objective: This qualitative study was imbedded in a randomized controlled trial evaluating the addition of geriatricians to usual care to enable the comprehensive geriatric assessment process with older patients on acute medical units. The qualitative study explored the perspectives of intervention participants on their care and treatment. Design: A constructivist study incorporating semi-structured interviews that were conducted in patients' homes within six weeks of discharge from the acute medical unit. These interviews were recorded, transcribed, and analysed using thematic analysis. Setting: An acute medical unit in the United Kingdom. Participants: Older patients ( n  = 18) and their informal carers ( n  = 6) discharged directly home from an acute medical unit, who had been in the intervention group of the randomized controlled trial. Results: Three core themes were constructed: (1) perceived lack of treatment on the acute medical unit; (2) nebulous grasp of the role of the geriatrician; and (3) on-going health and activities of daily living needs postdischarge. These needs impacted upon the informal carers, who either took over, or helped the patients to complete their activities of daily living. Despite the help received with activities of daily living, a lot of the patients voiced a desire to complete these activities themselves. Conclusions: The participants perceived they were just monitored and observed on the acute medical unit, rather than receiving active treatment, and spoke of on-going unresolved health and activity of daily living needs following discharge, despite receiving the additional intervention of a geriatrician.